Emerging Markets Integration in Latin America (MILA) Stock market indicators: Chile, Colombia, and Peru - Lizarzaburu Bolanos, Edmundo R. (2015)
This study aims to determine the impact of the Latin American Integrated Market (MILA) start-up in the main indicators of the stock markets of the countries that conform it (Chile, Colombia, and Peru). At the end, several indicators were reviewed to measure the impact on profitability, risk, correlation, and trading volume between markets, using indicators such as: annual profitability, standard deviation, correlation coefficient, and trading volume. The sample period runs from November 2008 to August 2013; and involves the three stock markets associated with MILA: Bolsa de Comercio de Santiago (BCS), Bolsa de Valores de Colombia (BVC) y Bolsa de Valores de Lima (BVL). An additional evaluation for further research would consist of the calculation of relevant indicators to corroborate the validity of the effects found in this investigation corresponding to the integration of the stock exchanges of Lima, Santiago and Bogota, after the integration of the Mexican stock exchange that occurred in 2014. Doi:  http://dx.doi.org/10.1016/j.jefas.2015.08.002